THE ACTIVITY BUDGET IN CUBAN HOTELS THAT USE THE «ALL INCLUSIVE» MODALITY (Costos y Gestión, 2020)
In this research, an Activity Based Budgeting procedure is designed, which helps to improve cost informationas a basis for analysis and control for decision making. It starts from a study on the budgeted costs in the Food and Beverage process in Cuban hotels that operate under the «All Inclusive» modality, taking as an examplethe Brisas Santa Lucia Hotel. The proposed procedure enriches the cost analysis by comparing it with ActivityBased Costing that is performed with the same level of detail of the information to strengthen cost controlthrough the basis of the causes of the deviations detected as a starting point for management decision making. The present work has been carried out with the intention of providing a tool for entrepreneurs in thehotel sector to improve the budgeting process in the Food and Beverage process, contributing to the management of their costs. The proposed procedure may be generalized in entities with similar characteristics.
Keywords: Activities; Activity Based Budgeting; Costs control; Decision making